Dénominations d’animés humains et dualité en anglais contemporain - Elise Mignot (Anglophonia)
Why can the noun phrase a German only denote a person (and not an object)? To refer to, say, a German desk, the lexeme /German/ takes the form of an adjective, not a noun. In the same way, why can a superior, where superior is a noun, only designate a person, and not, say, a book that is found better than another? Two problems arise simultaneously: the designation of humans, and the difference between two parts of speech (adjective and noun). Firstly, we suggest that nouns which designate humans are characterized by the notion of duality, understood as an all-or-nothing opposition between two items. Secondly, we propose that, within the domain of word-formation, nouns involve a notion of opposition. To test this, we focus on one type of secondary nouns, i.e. noun+noun compounds. If our hypothesis is valid, it probably reveals a tendency of nouns (i.e. nouns generally express opposition). It is then no surprise that lexemes which include a semantic feature of opposition (such as German, for example, which expresses nationality) are oriented towards the nominal category when used to designate humans.